Peran Sektor Pertanian Dalam Pertumbuhan Ekonomi Di Kawasan ASEAN - Rahman, Inayah; Pratiwi, Andini Cahyaning; Citaningati, Putri Rizka (Jurnal Ekonomi Pertanian dan Agribisnis, 2024)
ASEAN is an agricultural region that is abundant in natural products. In addition, this sector has contributed to economic growth in the ASEAN region through the availability of jobs and an increase in GDP. However, in recent years the productivity of the agricultural sector has shown a decline, which can affect economic growth. This study aims to determine the influence of the agricultural sector on economic growth in the ASEAN region. This study uses a quantitative method with panel data, namely annual data from 1997-2019 in 7 countries that are members of the ASEAN organization (Cambodia, Indonesia, Malaysia, Lao PDR, Philippines, Thailand, and Vietnam). Keywords: ASEAN, economic growth, agricultural sector. The data source for this research is annual data obtained from FAO and WDI. The analysis technique uses multiple linear regression tests using General Least Square Calculation (Cross Section SUR with Estimation Coefficient of Cross Section SUR (PSCE) with Eviews 9 software. Through this method, the result is that simultaneously all independent variables are significant in influencing the dependent variable. Or it can be explained that Agriculture Land, Employment in agriculture, and Agriculture, forestry, and fishing, value added have a significant effect on economic growth (GDP) in the ASEAN region.